PENGARUH PENGGUNAAN MEDIA VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA - Rostika; Uvia Nursehah; Avi Valentri (LPPM Universitas Cipta Mandiri, 2025)
One indicator of educational success is the use of educational media as a means of achieving the expected learning outcomes. The purpose of this study is to review research articles that discuss the currently popular learning video media. The articles reviewed in 2018-2023 using Google Scholar as a source. Then a classification is carried out based on the influence of learning media on the learning outcomes of elementary school students. This study uses the Systematic Literature Review (SLR) research method with the PRISMA (Preferred Reporting Items For Systematic Reviews and Meta Analyses) stages. The reviewed articles are in accordance with the research topic. The research results found ten articles that were in accordance with the research topic, namely the influence of video learning media which has been proven to improve student learning outcomes.